The role of KATP channels in cerebral ischemic stroke and diabetes - SZETO Vivian; CHEN Nai-hong; SUN Hong-shuo; FENG Zhong-ping (Acta Pharmacologica Sinica, 2018)
Abstract ATP-sensitive potassium (KATP) channels are ubiquitously expressed on the plasma membrane of cells in multiple organs, including the heart, pancreas and brain. KATP channels play important roles in controlling and regulating cellular functions in response to metabolic state, which are inhibited by ATP and activated by Mg-ADP, allowing the cell to couple cellular metabolic state (ATP/ADP ratio) to electrical activity of the cell membrane. KATP channels mediate insulin secretion in pancreatic islet beta cells, and controlling vascular tone. Under pathophysiological conditions, KATP channels play cytoprotective role in cardiac myocytes and neurons during ischemia and/ or hypoxia. KATP channel is a hetero-octameric complex, consisting of four pore-forming Kir6.x and four regulatory sulfonylurea receptor SURx subunits. These subunits are differentially expressed in various cell types, thus determining the sensitivity of the cells to specific channel modifiers. Sulfonylurea class of antidiabetic drugs blocks KATP channels, which are neuroprotective in stroke, can be one of the high stoke risk factors for diabetic patients. In this review, we discussed the potential effects of KATP channel blockers when used under pathological conditions related to diabetics and cerebral ischemic stroke.